Związki frazeologiczne z komponentem somatycznym jako nazwy uczuć w „Chłopach” Władysława Stanisława Reymonta - Błaszczyk, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The aim of the article is to present and analyze the selected phraseologisms with a somatic component naming feelings which were noted down from the novel of Władysław Stanisław Reymont entitled Chłopi (“The Peasants”). The analysis comprised 175 examples excerpted from the text, constituting just a part of collected research material. Compilation and organization of the exemplary material made it possible to assert that in the studied text the largest group constitute somatic phraseologisms being the designations of negative feelings and possessing in their lexical composition the noun serce (heart). Much less often there appear phraseologisms with other names of body parts, such as skóra (skin), gardziel (throat), głowa (head) or włosy (hair). In most cases the studied somatic phraseologisms occur in the canonical form, sometimes are creatively transformed by the author. In the studied material, the somatic phraseologisms designating positive feelings constitute a less numerous group. Also in this group, there dominate the compounds with a component serce (heart), while with other somatic components are less numerous. Also in this group, the idiomatic phrases occur in canonical forms or are creatively transformed by the author. Research conducted in the group of somatic phraseologisms designating emotional states enabled scholars to state that the novel of Reymont provides rich phraseological material in the form of canonical compounds, functionally justified innovation and metaphorical expressions, which, with respect to their structure and function, resemble phraseologisms. Among the phraseologisms where the writer’s intervention is noticeable, the author—at the level of language—refers to the world of values and cultural behaviours of peasant community of the village of Lipce. What is more, referring in the description of feelings to somatic phraseology, Reymont also emphasises a vital relationship between subjectively experienced feelings and an accompanying physiological reaction by an organism.